The Cat Who Walks Through Years: Chris Claremont's X-Men as Kitty Pryde's bildungsroman - Merchi, Samy (My University, 2016)
This dissertation examines the fictional character Kitty Pryde from the X-Men comic book series during the tenure of writer Chris Claremont. Claremont's work on the character primarily involves the years 1980-1990, though a return to writing the character in the 2000s is also discussed when relevant. The thesis question revolves around the definition of the bildungsroman genre and whether Claremont's narrative arc for Kitty Pryde's character fulfills that definition. Jerome Hamilton Buckley's 1974 book Season of Youth: The Bildungsroman from Dickens to Golding is used as the primary authority for the bildungsroman genre, and more specifically a list of nine criteria that Buckley deems particularly key to the definition of the genre. Each of the nine criteria is looked at in depth, demonstrating where and how they can be found in the narrative, if at all. However, because Buckley's perspective and criteria come from a time of less diversity, examination from a feminist and minority perspective is also added with ideas from Rita Felski and Stella Bolaki. Combining Buckley's initial list of nine criteria with more modern criticism, these ideas are then used to analyze Kitty Pryde's narrative arc and to determine whether it can be seen as a bildungsroman. The findings support reading Claremont's narrative arc of the Kitty Pryde character as a bildungsroman. Three of Buckley's nine key themes are identified as particularly prevalent in the narrative: the search for a vocation, ordeal by love, and the conflict of generations. Three more key themes are found to be less prevalent but still clearly present: the search for a working philosophy, the larger society, and alienation. Because Buckley's definition for the bildungsroman genre requires the presence of six of his nine key themes, the presence of the aforementioned six thus validate the reading of the narrative as a bildungsroman. The text also provides some suggestions for finding the three least applicable key themes within the narrative, but because their presence is not necessary to fulfill the definition of the bildungsroman, they are not rigorously examined. In addition to fulfilling Buckley's key themes, the paper also discusses the more modern minority-oriented views. It is shown how the narrative can be read in terms of a journey to diverge from norms, as per Felski's ideas of the unique qualities of the specifically female bildungsroman. As Kitty Pryde's narrative can be shown to conform to the bildungsroman ideas of both Buckley and Felski, the thesis question is thus answered positively: Chris Claremont's X-Men can indeed be read as Kitty Pryde's bildungsroman.